Methods to Measure Lipophagy in Yeast - Cristobal-Sarramian, A; Radulovic, M; Kohlwein, S D (Methods in enzymology, 2017)
Maintenance of cellular and organismal lipid homeostasis is critical for life, and any deviation from a balanced equilibrium between fat uptake and degradation may have deleterious consequences, resulting in severe lipid-associated disorders. Excess fat is typically stored in cytoplasmic organelles termed "lipid droplets" (LDs); to adjust for a constantly fluctuating supply of and demand for cellular fat, these organelles are metabolically highly dynamic and subject to multiple levels of regulation. In addition to a well-described cytosolic lipid degradation pathway, recent evidence underscores the importance of "lipophagy" in cellular lipid homeostasis, i.e., the degradation of LD by autophagy in the lysosome/vacuole. Pioneering work in yeast mutant models has unveiled the requirement of key components of the autophagy machinery, providing evidence for a highly conserved process of lipophagy from yeast to man. However, further work is required to unveil the intricate metabolic interaction between LD metabolism and autophagy to sustain membrane homeostasis and cellular survival.